Reliability analysis for distribution of power network - Olanrewaju, Rashidah; Amuda, Idowu Rahaman; Hassan Abdalla Hashim, Aisha (2021)
The benefits of reliability analysis for power distribution network can never be over oversized, which serves as a basis for the power system improvement and planning, it also increases the efficiency of distribution system. The system must be seen by the customers as what can be reducing the cost and improve reliability. But by getting the reliability done is not so easy due to the problems associated with getting the valid data. In order to have a power distribution analysis done as expected, having the information regarding each equipment on the data base is germane and the number of time the equipment has undergone a preventive examination is also important. That is the information regarding each equipment’s rate of failures, rate of repairs time and the rate of unavailability. These research study an analytic technique of solving complex distribution reliability evaluation of electric power system using MINNA DISTRICT PHCN, (Power Holding Company of Nigeria) as a case study. A result of the analysis from the system performance which shows the validity of analytical technique as a reliable analysis which is concerned with the system indices used